2020
DOI: 10.1101/2020.06.28.20141929
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outcomes and Cardiovascular Comorbidities in a Predominantly African-American Population with COVID-19

Abstract: Importance: Racial disparities in COVID-19 outcomes have been amplified during this pandemic and reports on outcomes in African-American (AA) populations, known to have higher rates of cardiovascular (CV) comorbidities, remain limited. Objective: To examine prevalence of comorbidities, rates of hospitalization and survival, and incidence of CV manifestations of COVID-19 in a predominantly AA population in south metropolitan Chicago. Design, Setting, Participants: This was an observational cohort study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…A total of 8350 records were obtained through systematic electronic searches and other ways. After screening titles, abstracts, and full texts, 9 studies [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ] with a total of 3449 COVID-19 patients were included in the meta-analysis. The essential characteristics of the included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 8350 records were obtained through systematic electronic searches and other ways. After screening titles, abstracts, and full texts, 9 studies [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ] with a total of 3449 COVID-19 patients were included in the meta-analysis. The essential characteristics of the included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 8 ] 2020 50 Retrospective cohort 66.3 ± 13.3 Severity 18 (36%) 32 (64%) Nguyen et al. [ 9 ] 2020 356 Retrospective cohort 61.3 ± 17 Mortality 90 (25.2%) 266 (74.8%) Rodriguez-Nava et al. [ 10 ] 2020 87 Retrospective cohort 67 ± 12.5 Mortality 47 (54%) 40 (46%) Wang et al.…”
Section: Resultsmentioning
confidence: 99%
“…The result of the meta-analysis of these seven studies performed in Western countries are reported in ►Fig. 2, [35][36][37][38][39][40][41] which demonstrate that COVID-19 patients taking statins had nearly 40% lower odds of progressing to the composite endpoint of severe/critical illness or death (OR: 0.59; 95% CI: 0.35-0.99; Cochran's Q p ¼ 0.02; I 2 ¼ 60%). Individually, six of these seven studies reported a reduced OR (i.e., OR < 1; protective effect of statins), [35][36][37][38][39][40] while in only one study was the OR >1 (i.e., OR: 1.60; 95% CI: 0.88-2.92).…”
Section: Resultsmentioning
confidence: 99%
“…Israel et al 16 split their database into two cohorts and reported two relative risk ratios for the outcome of mortality. Two studies, Grasselli et al 14 and Rodriguez-Nava et al 20 , reported on ICU patients; the other 11 7-10,13,15-19,21,22 reported on non-ICU patients. Six studies 7,10,17,18,20,21 defined a statin user as one who used statins after a COVID-19 hospitalization; seven studies 8,9,13-16,19,22 defined a statin user as one who used statins before a COVID-19 hospitalization.…”
Section: Resultsmentioning
confidence: 99%